2020
DOI: 10.1093/eurheartj/ehaa494
|View full text |Cite
|
Sign up to set email alerts
|

New-onset atrial fibrillation: incidence, characteristics, and related events following a national COVID-19 lockdown of 5.6 million people

Abstract: Aim To determine the incidence, patient characteristics, and related events associated with new-onset atrial fibrillation (AF) during a national COVID-19 lockdown. Methods and results Using nationwide Danish registries, we included all patients, aged 18–90 years, receiving a new-onset AF diagnosis during the first 3 months of 2019 and 2020. The main comparison was between patients diagnosed during lockdown (12 March 12–1 Apri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
85
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(98 citation statements)
references
References 22 publications
9
85
0
4
Order By: Relevance
“…According to a Danish study, following a national lockdown in Denmark, a 47% drop in registered new-onset atrial fibrillation cases was observed. The authors conclude that the risk of undiagnosed atrial fibrillation patients with complications could lead to worse outcomes in patients with atrial fibrillation in the COVID-19 pandemic [26].…”
Section: Arrhythmias In Covid-19mentioning
confidence: 97%
“…According to a Danish study, following a national lockdown in Denmark, a 47% drop in registered new-onset atrial fibrillation cases was observed. The authors conclude that the risk of undiagnosed atrial fibrillation patients with complications could lead to worse outcomes in patients with atrial fibrillation in the COVID-19 pandemic [26].…”
Section: Arrhythmias In Covid-19mentioning
confidence: 97%
“…Finally, a 47% drop in registered new-onset cases of atrial fibrillation was observed during the national lockdown in Denmark. In the event of prolonged or subsequent lockdowns, the risk of undiagnosed atrial fibrillation may also result in increased complications such as stroke, potentially translating into poorer outcomes in patients with atrial fibrillation during the COVID-19 pandemic [25]. Thus, to avoid unintended secondary effects of measures aiming at limiting the spread of SARS-CoV-2 on cardiovascular mortality, cardiologists and other health care practitioners should be alerted to develop complementary personalized approaches of patient care (e.g.…”
Section: Plos Onementioning
confidence: 99%
“…2 While the major focus of the health care system is on COVID-19, the number of reports on the decreasing rate of non-COVID-19-related conditions is increasing. 3,4 Renal colic with ureter stone is a common case in a daily urology practice. Although the ureteral stone disease gener-ally is an uneventful condition, it might be life-threatening if infection and/or renal impairment accompany.…”
Section: Introductionmentioning
confidence: 99%